Alarmins of the S100-Family in Juvenile Autoimmune and Auto-Inflammatory Diseases - Holzinger, Dirk; Tenbrock, Klaus; Roth, Johannes (Frontiers in Immunology, 2019)
Autoimmune and auto-inflammatory diseases in children are causing chronic inflammation, organ damage, and pain. Although several options for treatment are nowadays available a significant number of patients does not respond sufficiently to current therapies. In these diseases inflammatory processes are triggered by numerous exogenous and endogenous factors. There is now increasing evidence that especially a novel family of pro-inflammatory molecules, named alarmins, play a significant role in inflammatory processes underlying these diseases. Alarmins are endogenous proteins released during stress reactions that confer inflammatory signaling via Pattern Recognition Receptors (PRRs), like the Toll-like receptor 4 (TLR4). The most abundant alarmins in juvenile rheumatic diseases belong to the family of pro-inflammatory calcium-binding S100-proteins. In this review we will give a general introduction in S100-biology. We will demonstrate the functional relevance of these proteins in animal models of autoimmune and auto-inflammatory diseases. We will show the expression patterns of S100-alarmins and correlation to disease activity in different forms of juvenile idiopathic arthritis, auto-inflammatory diseases and systemic autoimmune disorders. Finally, we will discuss the clinical use of S100-alarmins as biomarkers for diagnosis and monitoring of rheumatic diseases in children and will point out potential future therapeutic approaches targeting inflammatory effects mediated by S100-alarmins.